PERANCANGAN FURNACE MULTIFUNGSI UNTUK GERABAH KERAMIK - Junita Sinaga, Erni (Industri Inovatif : Jurnal Teknik Industri, 2011)
Craftsmen ceramics industry (home industry) are usually produced goods and decorative ceramic pottery. In the ceramic combustion activity, the operator working position in a state squatting causing muscle fatigue, whereas for ceramic drying process is done by using sunlight energy. If the weather is cloudy then the drying process of ceramics can not be done thus inhibiting production. To overcome the above constraints, so that created a burning tool and ceramic dryer at once. The method used by anthropometric measurements to produce data with several percentiles (5%, 50%, 95%). The data used is the long reach of his hand forward, hand grip diameter, height and standing elbow height. Furthermore, comparing the standard time and standard output of the old equipment with new equipment. The results obtained by the ceramic combustion process is shorter, the combustion process in the old tool takes 8.07 hours while the new tool takes 3.67 hours per combustion. Output standard old tools produce 1.2 units per day, while the new equipment produces 2.7 units per day, so that profit a new tool showed an increase of 125%